Validated educational technologies for people with diabetes mellitus: Trends in brazilian graduate production (Research, Society and Development, 2021)
Objective: to identify the trends of scientific production in Brazilian postgraduate studies about educational technologies validated for people with diabetes mellitus. Method: this is a descriptive review, with a narrative approach. A search was carried out at the Bank of Theses and Dissertations of the Coordination for the Improvement of Higher Education Personnel, in order to identify the Theses and Dissertations on the proposed theme. The search was carried out in December 2020 and the strategies "educational technology AND diabet *" and "technology AND diabet *" were used. After selecting and applying the inclusion and exclusion criteria, 19 studies made up this review. Results: 17 dissertations and two theses were found. Studies from 2014 stand out, with predominance in the Northeast and Southeast regions. The contributions of educational technologies validated for people with diabetes mellitus point to the appreciation of the subjects' needs and professional experiences, empowerment for self-care, the need for behavioral changes and disease control and its complications. Conclusion: the health area produces works with the theme of validation of educational technologies, but with a sharp decrease in production about chronic diseases, especially diabetes mellitus.